How Country of Origin and Brand Image Shape Consumer Purchase Intention in the Skincare Market - Laura Martínez Ortega; Indah Julia Triandi (International Journal of Economics Business and Social Sciences, 2026)
The skincare industry has experienced significant growth in recent years, driven by increasing consumer awareness of personal care and product quality. In this competitive market, consumer perceptions play a crucial role in shaping purchasing decisions. Among the various factors influencing consumer behavior, country of origin and brand image are considered important determinants that affect how consumers evaluate skincare products and form purchase intentions. This research adopts a quantitative approach by collecting primary data through structured questionnaires distributed to consumers who are familiar with skincare products. The study examines how perceptions related to the origin of a product and the overall image of the brand influence consumer trust, product evaluation, and ultimately their intention to purchase. The data are analyzed using statistical methods to evaluate the relationships among the research variables and to determine the extent to which country of origin and brand image contribute to shaping consumer purchase intentions. The findings indicate that both country of origin and brand image have a significant influence on consumer purchase intention. Products originating from countries perceived to have strong reputations in the cosmetics industry tend to generate higher levels of consumer trust and positive product evaluations.